Foucault'nun biyo-politika kavramı ışığında filmlerde kürtaj temsili - Özcan, Fulya (My University, 2019)
FOUCAULT’NUN BİYO-POLİTİKA KAVRAMI IŞIĞINDA FİLMLERDE KÜRTAJ TEMSİLİ Bu çalışmada, Juno (2007), 4 Luni, 3 Saptamini şi 2 Zile (2007) ve Araf (2006) filmleri üzerinden, biyo-politikanın sinemadaki yansımalarını ve kürtaj temsillerini tartışmak amaçlanmıştır. İktidarın ve yönetimin kaynağına, “bir tür olarak insan”ın biyolojisini ve bedeni koyan biyo-politika kavramı, kürtajı tartışmaya elverişli bir temel sunduğundan seçilmiş, analizler, biyo-politikanın pratikleri ve iktidar sorgulamaları üzerinden temellenmiştir. Çalışmayı sınırlandırabilmek adına, kavram üzerinde en yoğun çalışan düşünürlerden biri olarak, Michel Foucault’nun biyo-politika kavramı seçilmiş, kürtajı anlamaya yönelik kavramsal temel, Foucault’nun biyo-politikası üzerinden oluşturulmuştur. Film incelemelerinde, toplumsal cinsiyet, kadın bedeni ve kadın bedenine müdahaleleri kuramlaştırması bakımından feminist film kuramı, görüntünün anlamını deşifre etmede sağladığı avantaj ve imkanlar dolayısıyla göstergebilim kullanılmıştır. Bu incelemelerle görülmüştür ki sinema filmleri, biyo-politikanın stratejilerinin hem deşifrecisi hem de yeniden üreticisi olabilmektedir. İktidarı deşifre eden örnekler, alternatif bir kürtaj temsili sunarken, mevcut söylemi tekrarlayan filmler, annelik, kürtaj gibi kadınlık deneyimlerini, iktidarın isteğine uygun inşa etmede bir araç haline gelmiştir. Bu inşada en yoğun kullanılan stratejilerinse özneleştirme, norm dışı bırakma ve delilikle eşleştirme olduğu tespit edilmiştir.

REPRESENTATION OF ABORTION IN FILMS IN THE LIGHT OF FOUCAULT’S CONCEPT OF BIOPOLITICS The aim of this study is to discuss the reflections of biopolitics in cinema and the representations of abortion through the films Juno (2007), 4 Luni, 3 Saptamini şi 2 Zile (2007) and Araf (2006). The concept of biopolitics, which places the body and biology of “the human as a species” in the source of power and management, was chosen due to providing a convenient basis for discussing abortion and was built on analyses, the practices of the biopolitics and power questionings. With an aim to limit the study, the concept of biopolitics of Michel Foucault, who is one of the philosophers working intensively on the concept, was chosen and the conceptual basis regarding the understanding of abortion was formed through the biopolitics of Foucault. In the film reviews, the feminist film theory was used in terms of theorizing the gender, woman body and the interventions to the woman body and semiotics was used thanks to its advantages and facilities in decoding the meaning of images. These reviews reveal that films can be both the decoders and remanufacturers of the strategies of the biopolitics. While the examples decoding power offer an alternative abolition representation, the films repeating the current discourse have become a tool for building the woman-related experiences like motherhood and abolition according to the desire of the power. It was detected that the most intensively used strategies in this building were subjectivation, anti-normalization and matching with madness.
Keywords: Abortion; Biyo-politika; Foucault; İktidar Biopolitic; Kadın; Kürtaj; Power; Sinema; Woman